PENGARUH MOTIVASI KERJA DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARAYAWAN PADA LPD SE-KECAMATAN TABANAN - Kadek Rista Ananda Putra; Nengah Landra; Ni Made Dwi Puspitawati (EMAS, 2022)
The purpose of this study is to find out the influence of work motivation and work experience on work productivity. This research was conducted on LPD in Tabanan Subdistrict. The results of researchers' observations to LPD in Tabanan Sub-District, seen some problems found such as: (1) employees are less eager at work due to lack of motivai from leaders. (2) Lack of work experience possessed by employees, resulting in a lack of mastery of knowledge and skills possessed. This study uses multiple linear analysis methods to find out the influence of work motivation and work experience on employee work productivity in LPD in Tabanan Sub-District. The sample in the study was 82 respondents. Sampling using saturated sampling techniques. The results of this study show that the variable (1) of work motivation has a positive and significant effect on employee work productivity where if work motivation increases then work productivity will also increase, (2) work experience has a positive and significant effect on employee work productivity where if work experience increases then work productivity will also increase. Assessment that work motivation and good work experience will increase employee work productivity in LPD in Tabanan Sub-District.